Removal of the endocarp in the emergence, vigor and pre-transplantation phenology of seedlings of seeds of nine coffee genotypes, in Oxapampa - Acosta-Trinidad, Luis (2022)
The objective of this research was to evaluate the emergence, vigor and pre-transplant phenology of seedlings from seed sown with and without endocarp, of nine coffee genotypes in Oxapampa, in order to have new genotypes of uniform seedlings. A randomized complete block experimental design with factorial arrangement was used. In the germinator, each experimental unit was made up of two rows with 25 seeds in each row. In storage, each experimental unit consisted of 16 pots: 4 pots were sampled. For the variables evaluated in germinator and storage, the genotypes that stood out were the following: UNACAF-89 (red caturra): percentage of emergence (57 %); growth rate (4.04 mm/week); UNACAF-116 (catimor): seedling fresh weight (0.64 g); seedling vigor index (53.79); fresh weight aerial part (2.36 g); fresh root weight (1.27 g); dry weight of the aerial part (0.53 g); root dry weight (0.16 g); root volume (1.25 ml); UNACAF-250 (obata): seedling dry weight (0.13 g); plant height (10.13 cm); UNACAF-188 (yellow caturra): emergence rate (1.17 plants/day) and UNACAF-213 (geisha): stem diameter (2.81 mm). In the group of seeds sown without endocarp, there were improvements for the variables: emergence percentage, emergence rate, seedling vigor index, fresh root weight and root volume. UNACAF-89 (red caturra) obtained the highest number of plants in secondary stages 09 and 10; likewise, the highest number of hypocotyls in secondary stage 07 of the BBCH scale.